Analisis Sektor Potensial Provinsi Jawa Tengah - Hastarini Dwi Atmanti; Jopie Tamtelahitu (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
Central Java province strives to always increase the potential of its sector. If the potential of the sector increases, then economic growth is created and public welfare increases. Inter-sectoral linkages can help to increase the potential of less potential sectors. Through proper planning policies, all sectors can potentially advance so that the welfare of society is created. The purpose of this study is to analyze the growth patterns and structure of each economic sector to estimate future economic growth prospects in the future, to analyze the dominant sectors of growth and growth potential and to analyze potential sectors based on growth criteria and contribution criteria. While the data used is Table Input Output Central Java 2013, Central Java GRDP 2007 - 2013, and GDP in 2007 - 2013. The method used Shift Share, LQ and Typology Klasen.